2021
DOI: 10.2147/nss.s278170
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Serotonin Transporter Gene and the Peripheral 5-Hydroxytryptamine in Obstructive Sleep Apnea: What Do We Know and What are We Looking for? A Systematic Review of the Literature

Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent disease with substantial public health burden. In most of the cases, there is a genetic predisposition to OSA. Serotonin/T-HydroxyTriptamine (5-HT) plays a key role in ventilatory stimulation, while the polymorphism of the serotonin transporter gene (STG) leads to alterations in serotonin level, making it important in OSA. Objective: To examine whether the 5-HydroxyTriptamine and the genetic predisposition influence the incidence and evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…In addition, researchers have also found that 5-HTT plays a crucial role in the study of limbic-frontal neural circuits ( 42 ); many studies have also focused on the activation of serotonin transporter ( 5 - HTTLPR ) polymorphisms in subregions in which the short (S) allele has been shown to reduce the transcriptional efficiency of the 5-HTT gene promoter ( 43 , 44 ). Studies have shown that the 5- HTTLPR gene polymorphism is associated with obstructive sleep apnea ( 45 ), female obsessive-compulsive disorder ( 46 ), postpartum depression ( 47 ), anorexia nervosa ( 48 ), and autism spectrum disorder ( 49 ) closely related. In addition, one study has demonstrated an increased risk of migraine in European women with the S allele ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have also found that 5-HTT plays a crucial role in the study of limbic-frontal neural circuits ( 42 ); many studies have also focused on the activation of serotonin transporter ( 5 - HTTLPR ) polymorphisms in subregions in which the short (S) allele has been shown to reduce the transcriptional efficiency of the 5-HTT gene promoter ( 43 , 44 ). Studies have shown that the 5- HTTLPR gene polymorphism is associated with obstructive sleep apnea ( 45 ), female obsessive-compulsive disorder ( 46 ), postpartum depression ( 47 ), anorexia nervosa ( 48 ), and autism spectrum disorder ( 49 ) closely related. In addition, one study has demonstrated an increased risk of migraine in European women with the S allele ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the genetic predisposition of the [32,33]. A meta-analysis by Maierean et al [34] of studies investigating serotonin polymorphisms showed the course of OSA and dependence on serotonin genetic modification. Thus, the prevalence of the L/L genotype in men is higher, which explains the male predisposition to OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The serotonin transporter gene polymorphism (SLC6A4) leads to changes in serotonin levels, which suggests that it is an important link in the pathogenesis of OSA [ 32 , 33 ]. A meta-analysis by Maierean et al [ 34 ] of studies investigating serotonin polymorphisms showed the course of OSA and dependence on serotonin genetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies involving monozygotic twins and siblings/children of persons with OSA have shown an up-to 50% increased odds of developing OSA compared to the general population (Ferini-Strambi et al 1995;Friberg et al 2009;Lundkvist et al 2012;Szily et al 2019). Additionally, numerous genetic studies (Palmer et al 2003;Patel et al 2007;Khalyfa et al 2008;Gozal et al 2007;Kalra et al 2008;Farias Tempaku et al 2020;Maierean et al 2021;Kerz et al 2021;Patel et al 2012) have identified several novel genetic loci associated with a sleep apnea phenotype suggesting around two-fifth (Casale et al 2009;Yue et al 2008;Yue et al 2005) of the OSA variance is attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 99%